Plasticized PVC‐Gel Single Layer‐Based Stretchable Triboelectric Nanogenerator for Harvesting Mechanical Energy and Tactile Sensing (Adv. Sci. 22/2022). Issue 22 (5th August 2022) - Park, Hyosik; Oh, Seung‐Ju; Kim, Daeyeong; Kim, Mingyu; Lee, Cheoljae; Joo, Hyeonseo; Woo, Insun; Bae, Jin Woo; Lee, Ju‐Hyuck
Abstract : Stretchable Triboelectric Nanogenerators In article number 2201070, Jin Woo Bae, Ju‐Hyuck Lee, and co‐workers report a plasticized poly(vinyl chloride) (PVC)‐gel single layer based stretchable triboelectric nanogenerator for mechanical energy harvesting and tactile sensing. The plasticized PVC‐gel is transparent and stretchable, has highly tribo‐negative property, and has improved electrical conductivity. It provides a novel approach of stretchable tactile sensor that can sense position and pressure without complicate electrode pattern.